Treatment of Delayed/Nonunion of Scaphoid Waist with Synthes Cannulated Scaphoid Screw and Bone Graft - Inaparthy, P. K. (Springer-Verlag, 2008)
Fracture of the scaphoid bone is the most common fracture of the carpus, and frequently, diagnosis is delayed. The unique anatomy and blood supply of the scaphoid itself predisposes to delayed union or nonunion. The Synthes scaphoid screw is a cannulated headed screw, which provides superior compression compared with some other devices used to internally fix scaphoid nonunions. Our aim was to conduct a retrospective study looking at the union rate, time to union, and complications and correlating the outcome of treatment against the delay between injury and surgery and location of the fracture within the bone. This study is a review of a cohort of 30 patients treated with a cannulated Synthes scaphoid screw and corticocancellous bone grafting for scaphoid waist delayed union and nonunion at our center. We achieved 86% overall union rate. The patients with delayed union achieved a 100% union rate. Three out of four patients with persistent nonunion after surgery reported no pain and improved function. The failure rate was 75% in patients who had sustained their fracture more than 5 years previously. Our study demonstrates that delayed union of scaphoid waist fractures and scaphoid waist nonunions present for less than 5 years can be successfully treated by fracture compression and bone grafting.